Alternatives to Fetal Bovine Serum in Different Cell Cultures (Global Journal of Medical Research, 2019)
Culture of animal cells is a key operation in bioscience at which fetal bovine serum is the most widely used. Other new alternatives were examined for growth of cell culture as newly born calf serum (NBCS), goat serum (GS) and Equine platelet lysate (EPL). Cell growth and viability was investigated in target cells (Vero-MDBK) using different concentration of alternatives. In general the platelet lysate medium 7 -10 % (EPL) supported cell growth and maintained viabilities comparable or superior to (NBCS). Goat serum exihbit heterologous cells in the first passage then the growth were similar to newly born calf serum with adding low concentration % of (GS). -5% & 6% up to 10% (GS) in MDBK and Vero cells respectively. 0.1% EPL could be used with lower % Goat serum to enhance cellular morphology.
Keywords: equine platelet lysate; goat serum; newly born calf serum; vero; MDBK; cellular viability; serum-free medium